Rape myth acceptance among law enforcement - Hebert, Racheal E (2013)
Research demonstrates a positive relationship between rape myth acceptance and sexist beliefs, as well as a negative relationship between rape myth acceptance and victim credibility. The current study assesses the interrelationships between rape myth acceptance, sexism, victim credibility, and victim empathy among law enforcement officers. Law enforcement officers’ individual characteristics are also assessed. An online survey was administered to 24 specialized sex crime law enforcement officers from a city in South Louisiana. There was no significant difference on measures of rape myth acceptance and sexism; however, individual items measuring victim credibility showed a distinct difference between law enforcement officers’ belief in credibility among traditional victims (i.e., professional women and virgins) and non-traditional victims (i.e., prostitutes and men). Due to the low sample size of this study, results must be interpreted with caution. Replication of this study is warranted with a larger and more diverse sample